John Bosco as Catholic Social Educator - Jovaiša, Leonas (Acta Paedagogica Vilnensia, 2000)
In this article is briefly stating the pedagogical experience and social education ideas of Saint Don Bosco. He devoted his life to educate the youth living in poverty.
Keywords: John Bosco; social education; religious education; Catholic pedagogy.